THE NON CRIMINAL PROSECUTION AREEMENT - da Silva, Marcelo Oliveira (2020)
This work aims to analyze the agreement of non-prosecution of the criminal procedure introduced in the national legal system by law no. 13,964/19. It is based on the investigation of the following problems: the objective of the decriminalizing measure, the competence and nuances on intertemporal law.